Long-term outcomes of single stenting compared with double stenting strategy for unprotected left main coronary artery disease: A protocol for systematic review and meta-analysis. Issue 52 (24th December 2020) - Wang, Jia-jie; Li, Xin; Yan, Dong-dong; Zhang, Zheng
Abstract: Background: The optimal interventions for unprotected left main coronary artery (ULMCA) disease have long been debated, and long-term clinical studies comparing single stenting to double stenting strategies for ULMCA are currently lacking. Methods: We plan to perform a systematic review and meta-analysis of clinical trials comparing single stenting with double stents strategy for ULMCA disease. We will search PubMed, EMBASE, Web of science and Cochrane Library using a comprehensive strategy. The related conference proceedings and reference lists of the included studies will also be checked to identify additional studies. Two reviewers will screen retrieved records, extract information and assess the risk of bias independently. STATA software will be used to conduct data synthesis. There is no requirement of ethical approval and informed consent. Results: This study will be submitted to a peer-reviewed journal for publication. Conclusion: We hope it will provide a relatively comprehensive reference for clinical practice and future relevant clinical trials. Ethics and dissemination: Ethics approval and patient consent are not required, as this study is a systematic review and meta-analysis. INPLASY registration number: INPLASY2020110030